FORMULASI NANOEMULGEL MINYAK ATSIRI PALMAROSA (Cymbopogon martinii) DAN AKTIVITAS ANTIINFLAMASINYA - Disa Andriani; Muhammad Saiful Amin (STIKES Cendekia Utama Kudus, 2023)
Palmarosa Essential Oil has the potential as an anti-inflammatory because it contains flavonoids, terpenoids, steroids. Nanotechnology can be used in dosage delivery systems, so that topical nanoemulgel preparations are made. This study aims to determine the physical quality of nanoemulgel and the effect of nanoemulgel preparations on anti-inflammatory effects in Wistar rats.The preparation of this nanoemulgel uses 3 formulas, with different ratios of Tween 80 and PEG 400, F1 tween 80 34% PEG 400 26%, F2 tween 80 36% PEG 400 24%, F3 tween 80 38% PEG 400 22%. The anti-inflammatory test method was carried out by subcutaneously inducing 2% carrageenin on the rat's back, resulting in edema formation. The data obtained was tested statistically with one-way ANOVA.The nanoemulsion characteristics test showed that all formulas were o/a type nanoemulsions, did not separate in the centrifugation test and the particle size was known to be F1 (149 nm), while F2 (136.6 nm) and F3 (132 nm). The physical quality test of nanoemulgel F1, F2, and F3 met all the requirements for a good physical quality test. The results of the F3 nanoemulgel anti-inflammatory test had the highest % inhibition of inflammation at 41.53% and based on statistical tests it was seen that the p-value 0.05 significance level which means not significantly different from the positive control